Efektivitas Layanan Bimbingan kelompok dengan Teknik Social Modeling untuk Meningkatkan Kepercayaan diri - Kukuh Anggar Dany; Siti Fitriana; Vesti Fresdiyati (Counseling Milenial (CM), 2024)
Confidence is a positive attitude of an individual that enables him to develop a positive assessment, both of himself and of the environment/situation he faces. Based on the results of observations, the provision of group guidance services to increase student self-confidence has never been carried out at Yayasan Pharmasi Semarang School. The purpose of this study was to describe the effectiveness of group guidance services using social modeling techniques to increase the self-confidence of class X students at SMK Yayasan Pharmasi Semarang. Quantitative research methods with true experimental research methods (true experimental design) with a pretest-posttest control group design. The results of this study are group guidance services using social modeling techniques to increase the self-confidence of class X students at SMK Yayasan Pharmasi Semarang more effectively carried out using social modeling techniques than without using social modeling techniques. The results of data analysis from SPSS showed that the average value of the control group before being given service was 110.70 and the average value of the experimental group was 111.70. After being given the service the average posttest score of the experimental group was 119.00 and 136.30 the average posttest value of the experimental group.